Economic Viability and Ecological Outcomes of Organic Horticulture: Evidence from Highland Farming Communities in Bali, Indonesia - Sukanteri, Ni Putu; Joshi, Ravindra Chandra; Yuniti, I Gusti Ayu Diah; Kamarudin, Ahmad Syazni (Journal of Tropical Crop Science, 2026)
Organic horticulture is an essential component of sustainable agriculture, offering agronomic, ecological, economic, and social benefits. This study investigates the economic viability and ecological outcomes of organic horticultural practices among highland farming communities in Bali, Indonesia. Utilizing a case study of certified organic farmer groups, data were collected via interviews, field observations, and secondary sources. Analysis included market trends, cost-benefit ratios, productivity, and environmental indicators. Findings show that organic horticulture enhances soil fertility with compost and manure, and manages pests through crop rotation, intercropping, and plant derived pesticides. Economically, organic horticulture is highly profitable, with a benefit-cost (B/C) ratio of 14.18, driven by strong consumer demand for pesticide-free produce in urban and tourist markets. Environmentally, organic farming reduces chemical contamination, boosts soil organic matter, and strengthens agroecosystem resilience. Socially, it promotes cooperative farming, knowledge sharing, and community engagement. Challenges include higher input costs, complex certification processes, and limited access to organic farming technology. This research’s novelty is its integrative assessment of agronomic productivity, environmental sustainability, and economic feasibility in a unique tropical context, offering a holistic sustainability model. Findings contribute to organic agribusiness theory, sustainable development, and resilient food system policymaking.